2014
DOI: 10.2134/jeq2012.0209
|View full text |Cite
|
Sign up to set email alerts
|

Simulation Climate Change Impact on Runoff and Sediment Yield in a Small Watershed in the Basque Country, Northern Spain

Abstract: Climate change is likely to have an impact on runoff and fluvial sediments in watersheds. These factors are among those used to characterize water bodies in relation to the European Water Framework Directive (WFD). Hence, it is important to investigate the extent to which climate change may hinder the achievement of the objectives of the WFD. We explored the potential impact of climate change on runoff and sediment yield for the Aixola watershed using the Soil and Water Assessment Tool (SWAT). The model calibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
47
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 71 publications
(83 reference statements)
8
47
0
1
Order By: Relevance
“…The model was selected because it is a dynamic simulation model able to simulate streamflow response to climate change, it is in the public domain, and the generation of input files is eased by GIS-based tools. Although it is frequently applied to medium and large catchments with reasonably good results, it has also been calibrated for small forest catchments with good results [7,22], i.e., with semi-natural land use. So, the SWAT model can be applied for hydrologic simulation in small catchments under different climatic conditions.…”
Section: The Swat Hydrological Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The model was selected because it is a dynamic simulation model able to simulate streamflow response to climate change, it is in the public domain, and the generation of input files is eased by GIS-based tools. Although it is frequently applied to medium and large catchments with reasonably good results, it has also been calibrated for small forest catchments with good results [7,22], i.e., with semi-natural land use. So, the SWAT model can be applied for hydrologic simulation in small catchments under different climatic conditions.…”
Section: The Swat Hydrological Modelmentioning
confidence: 99%
“…Various approaches to assess the effects of climate change on water resources have been used [5][6][7][8]. In general, studies have reported that an increase in CO2, as long as temperature and rainfall remain constant, will cause increases in water yield due to the marked decrease of the stomatal conductance of plants, thus decreasing evapotranspiration [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…All sectors depending on water availability are now vastly exposed to the climate change impacts [5]. Hence, climate change can also impact sediment export [6,7], crop yield and biomass [8,9], water quality [10], etc. All these are driven by streamflow.…”
Section: Introductionmentioning
confidence: 99%
“…Climate models estimate [2][3][4][5][6][7][8] that the global average temperature is likely to increase 4.0 • C by the conclusion of the 21st century [9]. Reliable prediction of climate is pre-requisite to comprehend its impacts on hydrology and water resources [10].…”
Section: Introductionmentioning
confidence: 99%